Neuron-Specific Vitamin D Signaling Attenuates Microglia Activation and CNS Autoimmunity - Lee, Priscilla W.; Selhorst, Amanda; Lampe, Sara Gombash; Liu, Yue; Yang, Yuhong; Lovett-Racke, Amy E. (Frontiers in Neurology, 2020)
Low vitamin D during childhood is associated with an increased risk of developing multiple sclerosis (MS) as an adult. Given that vitamin D has anti-inflammatory properties, it has been postulated that the relationship between MS and low vitamin D is due to immune dysregulation. Since the vitamin D receptor (VDR) is expressed in many cell types, this study investigated an alternative hypothesis—neuron-specific VDR signaling induces anti-inflammatory molecules that protect the central nervous system from autoimmunity. Using media from neurons treated with calcitriol, the active form of vitamin D3, LPS-activated microglia had a reduction in pro-inflammatory molecules, and a reciprocal induction of anti-inflammatory molecules. Since IL-34 is critical to the homeostasis of microglia, and was previously shown to be induced in endothelial cells by vitamin D, we investigated IL-34 as the potential anti-inflammatory molecule induced in neurons by vitamin D. Treatment of LPS-activated microglia with IL-34 reduced pro-inflammatory cytokine production and enhanced the expression of anti-inflammatory transcripts. However, neutralizing IL-34 in vitamin D neuronal conditioned media only impacted IL-6 and not the broader anti-inflammatory phenotype of microglia. To mimic low vitamin D in children, we used a neuron-specific inducible mouse model in which VDR was partially deleted in juvenile mice. Partial deletion of VDR in neurons during early life resulted in exacerbated CNS autoimmunity in adult mice. Overall, the study illustrated that vitamin D signaling in neurons promotes an anti-inflammatory state in microglia, and low vitamin D in early life may enhance CNS autoimmunity.